2016
DOI: 10.1016/j.chom.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of War and Truce between Mosquitos and Emerging Viruses

Abstract: Arboviruses have made unexpected reappearances in recent years. Unlike viruses that undergo direct transmission, arboviruses utilize an arthropod vector (e.g., mosquitos, sandflies, and ticks) to spread throughout human populations. Here, we provide a snapshot of mosquito susceptibility to viral infection using flaviviruses, alphaviruses, and bunyaviruses as examples of emerging pathogens of global health relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Despite the potential effectiveness of TBVs against viruses, this approach is still at its developmental stage and needs more improvements [ 4 ]. Mosquito-borne viruses such as WNV are enveloped with a cytoplasmic cycle for replication [ 10 , 11 ], adapted to both mosquitoes and vertebrates and thus, use evolutionarily conserved pathways shared by both hosts [ 12 ]. It has been revealed that some proteins in arthropods/mammals, which are named C-type lectins, are employed as receptors to facilitate the invasion of arboviruses [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential effectiveness of TBVs against viruses, this approach is still at its developmental stage and needs more improvements [ 4 ]. Mosquito-borne viruses such as WNV are enveloped with a cytoplasmic cycle for replication [ 10 , 11 ], adapted to both mosquitoes and vertebrates and thus, use evolutionarily conserved pathways shared by both hosts [ 12 ]. It has been revealed that some proteins in arthropods/mammals, which are named C-type lectins, are employed as receptors to facilitate the invasion of arboviruses [ 13 ].…”
Section: Introductionmentioning
confidence: 99%